Category of evaluation as the object of linguistics: prospects of communication aspects of study - Prihodko, Anna; Prihodko, Ganna Illivna; Prihodko, G. I.; Prihodko, Ganna; Приходько, Ганна; Приходько, Анна Ильинична; Приходько, Анна (Одеса, 2018)
У статті розглянуто категорію оцінки як одну з функцій мови, важливе і цікаве явище в лінгвістиці. Оцінювання різних фрагментів світу - безсумнівно, значуща складова когнітивної діяльності людини. Оцінка реалізується свідомістю суб'єкта при сприйнятті і обробці інформації про зовнішній світ і співвідноситься з внутрішнім (мовним) світом людини, відображаючи його «картину світу». Сутність категорії оцінки пояснюється теорією ціннісної спрямованості людської діяльності та свідомості, а коло її характеристик обіймає все те, що задано фізичною й психічною природою людини, її буттям і відчуванням. Оцінювання виступає різновидом пізнавальної діяльності, адже у гносеологічному плані будь-який пізнавальний акт виражає ставлення суб'єкта до об'єкта, тобто містить акт оцінки. Оцінне трактування особи, обставин, предмета є одним із найважливіших видів розумово-мовленнєвої діяльності в повсякденному житті особистості. У праці пропонується комунікативний підхід до дослідження оцінних явищ, які існують в реальності і відображаються в мові. Комунікативний аспект мови означає наявність єдиної структури мовних одиниць, скріплених зв'язком змістовних і формальних сторін. У зв'язку з цим особливої значущості набуває функціонування оцінних висловлювань, оскільки оцінювання різних фрагментів світу є однією з найважливіших складових когнітивної діяльності людини. Оцінка повинна вивчатися комплексно та вичерпно як категорія високого рівня абстрагування, яка належить до числа тих категорій, які задані суспільною, фізичною та психічною природою людини, що зумовлює її ставлення до інших індивідів та предметів навколишньої дійсності.

The paper is aimed at studying the category of evaluation, a very important and interesting phenomenon in linguistics. Evaluation of different world's fragments is, of course, a considerable part of human cognitive activity. Evaluation is realized by subject's consciousness in the perception and processing of information about the outside world and relates to internal (linguistic) world of man, reflecting his "view of the world." The essence of the category of evaluation is explained by the theory of value orientation of person’s activity and consciousness, and the range of its characteristics embraces all that is given by the physical and mental nature of man, his being and feeling. Evaluation is as a kind of cognitive activity, as in epistemological terms, any cognitive act expresses the attitude of the speaker to the object described, that is, contains an act of evaluation. Evaluative interpretation of circumstances, subjects is one of the most important types of mental-speech activity in everyday life of an individual. The article proposes the communicative approach to the research of evaluative phenomena that exist in the reality and are reflected in language. The communicative aspect of the language means the existence of a unified structure of the linguistic units, bound by the connection of meaningful and formal sides. In this regard, the functioning of evaluative utterances acquires special significance, because the evaluation of various fragments of the world is one of the most important components of individual’s cognitive activity. The evaluation should be studied comprehensively and profoundly as a category of high level abstraction as one of the categories given by the social, physical and mental nature of a person, which determines his relation to other individuals and objects of the surrounding reality.
Prihodko, Anna. Category of evaluation as the object of linguistics: prospects of communication aspects of study / A. Prihodko // Одеський лінгвістичний вісник. – 2018. – Вип. 11. – С. 64-70. D0I https://doi.org/10.32837/2312-3192-2018-11-64-70
Keywords: Research Subject Categories::HUMANITIES and RELIGION; Картина світу; когнітивна діяльність; оцінка; функції мови; комунікація; World view; cognitive activity; value; language functions; communication